Fuelling the Fire: Mitochondrial Fuel Selection for Sustaining Shivering Thermogenesis in the High-Altitude Deer Mouse, Peromyscus Maniculatus - Baragar, Claire Eugenie (My University, 2023)
High altitude is characterized by chronically low ambient temperatures and oxygen. To survive, highland native deer mice (Peromyscus maniculatus) are capable of high rates of prolonged thermogenesis due to elevated aerobic capacity (V̇O2max) in hypoxia. Deer mice primarily use fats to fuel their high metabolic rates for heat production. Carnitine palmitoyl-transferase 1 (CPT-1) is a rate-limiting step in mitochondrial fat oxidation, and a reduction in CPT-I sensitivity for its substrate L-carnitine is associated with a reduction in muscle fat use during high intensity exercise in mammals. Sensitivity of mitochondrial metabolism to ADP also changes with exercise. It is currently unknown whether similar mechanisms underpin regulation of fuel use during shivering, but I predicted that sensitivities to ADP and L-carnitine would be greater in highlanders than lowlanders and increase with acclimation. To address this question, I examined mitochondrial sensitivity to substrates involved in the fat oxidation pathway in low- and high- altitude deer mice born and raised in common laboratory conditions. Mice were also acclimated to high altitude condition of cold hypoxia to examine if the plasticity of these traits were affected by altitude ancestry. Consistent with previous findings, both high and lowland mice increased their cold-induced V̇O2max following cold hypoxia acclimation and rely primarily on lipids to fuel thermogenesis. High- and low-altitude deer mice responded differently to chronic cold hypoxia with highlanders showing a ~7-fold greater ADP sensitivity than lowlanders following acclimation. In contrast to the expected outcome, highlander deer mice tended to have a reduced sensitivity to L-carnitine compared to lowlanders that approached statistical significance. Neither sensitivity to palmitoylcarnitine sensitivity nor mitochondrial expression of FAT/CD36, thought to aid in mitochondrial fat delivery, showed differences between population or changes with acclimation, indicating that limitations to lipid oxidation during shivering likely occur at, or upstream of, CPT-I in the deer mouse.
Keywords: Mitochondria, high altitude, thermogenesis, hypoxia, lipids, CPT-I